TYPOLOGY AND ANALYSIS OF INTERNATIONAL EDUCATIONAL ACTIVITY OF RUSSIAN UNIVERSITIES - Alisa V. Melikyan (Высшее образование в России)
Abstract. The objective of the study was to identify the groups of higher education institutions having similar indicators of international educational activities, and analyze their characteristics. In the framework of the research the statistical data on indicators of international educational activities of Russian universities and branches were collected, processed and systematized. The cluster analysis of 362 universities and 28 branches was conducted on the basis of indicators that evaluate the state of their international educational activity: the number of foreign undergraduate, graduate and mobile students and the number of double-degree international programs.The cluster analysis has identified five groups of higher education institutions with similar characteristics: «outsiders», «recruiters of international students», «diversificators», «strategists» and «national leaders». The study confirmed the absence of a direct relationship between university’s activity is in realizing international educational activities and the income that it receives from this practice. The revenues of universities from one cluster may be incommensurable. This is due to the difference in the tuition fees and the receipt of income from the provision of additional educational services to foreign students.The resulting classification of higher education institutions can be considered in the development of targeted governmental actions that support higher education institutions in their efforts to increase the competitiveness in the international education market. It may also be of interest to Russian university managers as it provides an overview of the main directions of development and the results of international educational activities of the competing universities.